The effect of revaluation and implementation of accounting management information system of state-owned assets on the quality of financial report (Asian Journal of Economics and Business Management, 2022)
The benefit that the state gets from the revaluation of SOA is to get the updated value of assets in the financial report in accordance with their fair value. In addition, quality spending is the creation of cost savings from maintenance expenditure efficiency because the inventory results produce updated SOA condition data. Then, decision-making in the management of SOA could be better and supports the asset function as a revenue center. The SOA revaluation is also useful to support state budget financing resources in the form of providing SOA as an underlying asset of issuance. This study to determine the effect of the revaluation and implementation of the Management Accounting Information System of State-Owned Assets (SOA) on the quality of the financial report. This research was conducted at The Office of State Asset and Auction Service (KPKNL) Bandar Lampung using primary data collected from the distribution of questionnaires and interviews. The population in this study was all KPKNL Bandar Lampung employees, there are 34 people, which the population was taken as research samples. The data analysis was made using Partial Least Square with revaluation and implementation of SIMAK as the independent variables and quality of the financial report as the dependent variable. The data analysis instrument was using Smart-PLS 3.3.9 version. The results of this study show that the revaluation of state-owned asses had no significant effect on the quality of the financial report and the implementation of accounting management information system for state-owned asset (SIMAK-SOA) had a significant effect on the quality of financial report. From this research, it can be obtained that there are evaluations and improvements that need to be made by SOA management and can be a source of knowledge about SOA for the community in order to help supervise SOA management. Furthermore, researchers are expected to be able to add to the types of variables that have been presented in this study and expand the research subject.